Development of a modified drinking water quality index (MDWQI) and its application for assessing water quality in groundwater resources of Iran - Mohaad-Reza Mohebbi (سلامت و محیط, 2013)
ABSTRACT Background and objectives: In this research, an innovative drinking water quality index for assessing water resources as “modified drinking water quality index (MDWQI)” was developed and applied for evaluating all of the groundwater resources utilized for community water supply in urban areas of Iran during 2011. Materials and methods: Twenty-three water quality parameters and relevant Iranian standards for drinking water quality were selected as input parameters and benchmarks respectively. The MDWQI is calculated using three factors including the number of parameters that excurse benchmarks, the number of measurements in a dataset that excurse benchmarks and the magnitude of excursions. The MDWQI scores range from 0 to 100 and classify water quality in five categories as excellent (95-100), good (80-94), fair (65-79), marginal (45-64), and poor (0-44). Results: According to the MDWQI value, about 95% of the groundwater resources were in the good condition and the others were in the fair or marginal condition; also the best and the worst water quality of water resources were observed in Ardebil Province and Qom Province respectively. The three parameters of fluoride, magnesium, and nitrate recorded the highest rates of violation to be 74, 32, and 13% respectively. Conclusion: The nationwide average score of the MDWQI was 85 (good description). This study indicated that the MDWQI and its sub-indices could describe the overall water quality of water bodies easily, reliably and correctly and have the potential suitability for extensive application all over the world.